Information and knowledge leakage in supply chain - Tan, Kim Hua; Wong, W.P.; Chung, Leanne (Springer, 2016)
The current world of post industrial value generation sees companies increasingly analyzing their internal operations against their external organizations to identify supply/demand fluctuations along the supply chain. Within these integrated relationships between internal and external parties in the supply chain, knowledge and information have become very important production resources. The existence and success of an increasing number of organizations strongly depend on their capabilities to utilize knowledge and information for profit generation. By managing more efficient information sharing, the volume of company confidential information passing through the supply chain increases, and this brings about more incidences of knowledge leakage and information leakage. A survey by PricewaterhouseCoopers in 2014 shows information security spending over the next 12 months would increase 60.27 % in Asia and 48.98 % in all regions. This emphasizes the importance of information privacy and therefore the necessity to study the information and knowledge leakage in integrated supply chain. The objectives of this study are to investigate the factors triggering information and knowledge leakage and create a mitigation framework to soften the impact of leakages on performance. The above objectives will be met by formulating and examining several hypotheses of a conceptualized information leakage (IL) and knowledge leakage (KL) framework. A case study derived from a structured interview is adopted as a methodology in this research. As a result, this paper contributes a novel theoretical model that characterizes information and knowledge leakage in an integrated supply chain. Therefore, it also adds new knowledge of managing information and knowledge leakage to supply chain management.